2022
DOI: 10.1186/s40545-022-00421-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-care practice among adult hypertensive patients at ambulatory clinic of tertiary teaching Hospital in Ethiopia: a cross-sectional study

Abstract: Background Globally, hypertension is a major public health problem and a strong predictor of cardiovascular disease complications. To reduce and prevent complications from hypertension, it is important to adapt self-care behaviors. This study aimed to assess the self-care practices of adult hypertensive patients at a tertiary teaching hospital in Ethiopia. Methods A health facility-based prospective cross-sectional study was conducted at Jimma Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…A study from southwest of Ethiopia reported a level of self-care practice by hypertensive patient of 46.9%. Thus, which is consistent with the current finding [ 30 ]. Moreover, a study from Nepal reported a comparable proportion (52.2%) of hypertensive patients having a consistent level of self-care practice [ 31 ].…”
Section: Discussionsupporting
confidence: 94%
“…A study from southwest of Ethiopia reported a level of self-care practice by hypertensive patient of 46.9%. Thus, which is consistent with the current finding [ 30 ]. Moreover, a study from Nepal reported a comparable proportion (52.2%) of hypertensive patients having a consistent level of self-care practice [ 31 ].…”
Section: Discussionsupporting
confidence: 94%
“…Despite the robust evidence of self-care behaviours in controlling high BP, adherence to self-care behaviours is generally poor 15–20. Only 38% of treated patients with hypertension in Nepal have their BP under control, underscoring the need for effective strategies to improve the hypertension care cascade 5.…”
Section: Introductionmentioning
confidence: 99%
“…H-SCALE has six domains which contain medication adherence (3 items), low-salt diet (12 items), physical activity (2 items), smoking (1 item), weight management (10 items), and alcohol (1 item). All self-care domains had acceptable reliability in previous studies in Ethiopia (7,15,54). The Cronbach's alpha of medication adherence, low salt, physical activity adherence, weight management, and alcohol use were 0.94, 0.74, 0.81, 0.93, and 0.92, respectively (22).…”
Section: Data Collection Procedures and Instrumentmentioning
confidence: 75%